Bond strength of different orthodontic brackets produced with different materials and fabrication methods - de Souza Araújo, Isaac Jordão; Matté Zanini, Maurício; Favarão, Jamille; Puppin Rontani, Regina Maria; Bortolazzo Correr, Américo; Coelho Sinhoreti, Mário Alexandre (Brazilian Dental Science, 2022)
Objective: The aim of this study was to evaluate the effects of material and processing methods on the bondstrength of orthodontic brackets. Material and Methods: Five types of brackets were tested: Conventionalmetallic (CM), metallic sandblasted (SB), ceramic (C), polycarbonate (PC), and metallic fabricated by meltinginjection molding (MIM). Shear bond strength (SBS) was conducted to check bond strength of the bracketsbonded to bovine teeth (n=10/group), and tensile bond strength (TBS) (20 brackets/group) to check bracketretention to bonding material (n=20/group). Both, SBS and TBS were conducted with 1mm/min crossheadspeed in a universal testing machine. Bond strength was calculated in Megapascal (MPa) based on force (N) andbracket area (mm2). Data normality was verified, and One-way ANOVA was the statistical test with Tukey posthoc(a=0.05). Results: SB and MIM presented higher SBS compared to C, PC, and CM (p